Equality and diversity in research: building an inclusive future - Michael El Boghdady (BMC Research Notes)
Abstract Research progress and innovation are hindered by barriers, inequalities, and exclusions within academia. Embracing equality, diversity, and inclusion (EDI) is not only an ethical imperative but also essential for advancing knowledge and addressing global challenges. EDI principles ensure that researchers from all backgrounds have equitable opportunities to contribute to and benefit from research. Despite recent efforts to improve inclusivity, systemic barriers such as bias in funding, publication, and representation still persist. Strategies to address these include diverse recruitment, mentorship programmes, training to mitigate unconscious bias, and promoting data transparency. Institutional leadership plays a pivotal role in fostering an inclusive culture by setting clear goals and ensuring accountability. Promoting EDI in research enhances scientific excellence, aligns with human rights principles, and ensures equitable benefits for global populations, reflecting the richness of diverse perspectives in academic pursuits.